Clinical Practice Guidelines Infective Endocarditis Treatment. - Lázaro de la Cruz Avilés; Francisco de Jesús Valladares Carvajal; Brandy Viera Valdés; Pablo Rodríguez Díaz (Medisur)
Clinical Practice Guidelines for Infective Endocarditis Treatment. Infectious disease affecting the endocardium produces vegetations and could also affect the septum, the chordae tendinae or mural endocardium. It includes concept, risk factors, classification (and special groups) and an update and review of the main clinical aspects, complications and treatment stressing the antibiotic therapy. It includes assessment guidelines focused on the most important aspects to be accomplished.